بے اولاد افراد کو درپیش مسائل اوران کاحل: اسلامی تعلیمات کی روشنی میں ایک مطالعہProblems faced by Childless persons and their Solutions: A Study in the light of Islamic teachings (Al-Qamar, 2022)
A person’s life will be filled with a variety of social, economic, and intellectual challenges. There are certain issues that a person can handle using his intellect, intelligence, and physical struggle, yet there are some issues that are out of a person’s control. Childlessness is one of them. This is a problem that leads to a lot of family and psychological problems in matrimonial life. A person's sexual self-esteem, desire, and performance can all be impacted by infertility. Sex is a common method used by couples to emotionally connect. Couples may lose that emotional bond if sex is seen as a failure or a letdown. In Europe, the situation is different, however, in Pakistani society, it is a very severe issue. Childless people use a variety of less ethical methods—methods other than treatment—to make up for this lack. Islam is the only religion that can appropriately counsel such individuals and provide them comfort in such a situation. It offers an answer to every issue facing modern civilization. In this short research paper, Islamic teachings have been described in this regard so that the heart of childless people can be mitigated.
Keywords: Social issues; Childlessness; Islamic teachings